Determination of Ascorbic Acid with Wells-Dawson Type Molybdophosphate in Sequential Injection System - Vishnikin, Andriy; Вішнікін, Андрій Борисович; Sklenářová, Hana; Скленаржова, Хана; Solich, Petr; Соліч, Петро; Petrushina, Galina; Петрушина, Галина Олександрівна; Tsiganok, Ludmila; Циганок, Людмила Петрівна (Taylor & Francisco Online, 2011)
Two-electron reduced heteropolyblue is formed very fast at pH 3.75–4.75 in the reaction between Dawson-type molybdophosphate HPA and ascorbic acid (AsA) (ϵ814 = 1.15 × 104 L • mol−1 cm−1). Simple, fast, and direct SIA method for AsA determination was developed. Under found optimal conditions, linear calibration curve was obtained over the range 3 × 10−6–3.5 × 10−4 mol L−1 AsA, and detection limit (3 s) was 1 × 10−6 mol L−1. The proposed SIA method has high sample throughput of 60 h−1 and small reagent consumption. The procedure was applied to the analysis of pharmaceuticals and juices. Двоелектронний відновлений гетерополісиній утворюється дуже швидко при рН 3,75–4,75 у реакції між молібдофосфатом типу Доусона й аскорбіновою кислотою (AsA) (ϵ 814 = 1,15 × 10 4 л • моль −1 см −1 ). Розроблено простий, швидкий і прямий метод SIA для визначення AsA. За знайдених оптимальних умов отримано лінійну калібрувальну криву в діапазоні 3 × 10 −6 –3,5 × 10 −4 моль Л −1 AsA, а межа виявлення (3 с) становила 1 × 10 −6 моль Л −1 . Запропонований метод SIA має високу пропускну здатність проби 60 год -1 і малу витрату реагенту. Процедура була застосована для аналізу фармацевтичних препаратів і соків.
Визначення аскорбінової кислоти молібдофосфатом типу Веллса-Доусона в системі послідовного введення
Keywords: Ascorbic acid; аскорбінова кислота; Dawson's heteropolymolybdate; гетерополімолібдат Доусона; fruit juice; фруктовий сік; pharmaceutics; фармацевтика; sequential injection analysis; аналіз послідовного впорскування